Business communication : for BBA - Kumar, Varinder (Kalyani Publisher, 2010)
Business communication : for BBA / Kumar, Varinder. -- Kolkata: Kalyani Publisher, 2010 428 K97e2 2nd ed. No. of Copies : 1